2023
DOI: 10.2196/43213
|View full text |Cite|
|
Sign up to set email alerts
|

The Longitudinal Impact of Social Media Use on UK Adolescents' Mental Health: Longitudinal Observational Study

Abstract: Background Cross-sectional studies have found a relationship between social media use and depression and anxiety in young people. However, few longitudinal studies using representative data and mediation analysis have been conducted to understand the causal pathways of this relationship. Objective This study aims to examine the longitudinal relationship between social media use and young people’s mental health and the role of self-esteem and social conn… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…In the UK, most adolescents (98%) own a smartphone, and are reported to be active users of social media (93%),14 with comparable trends reported in other Western populations 15. Samples in the USA and the UK (2021–2022) estimate that the time adolescents spend on smartphones and social media ranges between one and a half hours and eight and a half hours per day,12–14 16 17 with most adolescents spending between 1 and 3 hours per day 14 16 17. Problematic social media use is also prevalent, with 12% of adolescents in England reported to exhibit addictive use behaviours 18…”
Section: Introductionmentioning
confidence: 73%
See 1 more Smart Citation
“…In the UK, most adolescents (98%) own a smartphone, and are reported to be active users of social media (93%),14 with comparable trends reported in other Western populations 15. Samples in the USA and the UK (2021–2022) estimate that the time adolescents spend on smartphones and social media ranges between one and a half hours and eight and a half hours per day,12–14 16 17 with most adolescents spending between 1 and 3 hours per day 14 16 17. Problematic social media use is also prevalent, with 12% of adolescents in England reported to exhibit addictive use behaviours 18…”
Section: Introductionmentioning
confidence: 73%
“…In moderation, smartphone and social media use (eg, <2 hours per day) can be advantageous for mental well-being and mental health,19–24 as well as other associated health and behavioural outcomes (eg, sleep, physical activity, classroom behaviour and attainment). However, at higher levels of use, the reverse effect tends to be seen, with increasing time spent on smartphones and social media associated with decreasing levels of mental well-being and higher levels of anxiety and depression 17 19–21 23 25 26. Poor academic performance, disruptive classroom behaviour and less time spent in physical activity and sleep are also more likely in adolescents who spend a greater proportion of time on smartphones and/or social media 19–23 25 26.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 33 studies were included in this scoping review, with 26 of them were cross-sectional in nature, indicating a snapshot overview of the relationship between SMU, sleep, and mental health. Moreover, only a few studies utilized representative samples [ 35 , 36 , 40 , 41 ], as outlined in Table 1 . It is also worth noting that the sample sizes varied significantly across studies, ranging from 54 to 195,668 participants.…”
Section: Overview Of Recent Studiesmentioning
confidence: 99%
“…Four longitudinal cohort studies reported mixed findings between SMU and mental health [ 41 , 63 , 64 •, 65 ]. Two cohort studies conducted in the USA and China reported that frequent and problematic SMU were significantly associated subsequent mental health issues [ 64 •, 65 ].…”
Section: Synthesis Of Recent Findingsmentioning
confidence: 99%
“…Most existing data on social media or smartphone use and mental health problems in young people, including self-harm, are from cross-sectional studies, some of which have repeated waves [ 12 , 13 ]. Most studies have considered self-reported time spent on social media, rather than the nature or quality of activity, or objective measures of online activity.…”
Section: Introductionmentioning
confidence: 99%